(3cJGH GdeMHI hGdThb hGdGfS hGdQVGs - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fRg bdhH ChdjGFg Yf GdEdJaGJ Edi eJGY GdOfjG CeG HYO aEf GdeMHI ddg JYGdi gi GdZGjI GdbUhi ef GdebGeGJ hGdKQhI GdYdjG s
(3BNQgG (B:s
(3hjbGd GdThb fGQ Gddg JYGdi GSJYedgG ai bdhH ChdjGFg ced cJGH GdeMHI hGdThb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(3 /433) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs